(Re)configurações do agir modelagem na formação continuada de professores de matemática da educação básica - Bonotto, Danusa de Lara (2017)
The present research deals with the mathematical modeling in mathematical education and Continuing education of teachers. It is linked to the line of research, teaching and Teacher Education in Science and Mathematics from the Graduate program in Science and Math Education at the Pontifical Catholic University of Rio Grande do Sul – PUCRS. This research aims to understand how the Act modeling - work of professor of Mathematics with modeling, is (re)configured in the texts produced by professor of Mathematics during the experiences with mathematical modeling and modeling in education. To do this, the methodological-theoretical and analytical contribution of Interactionism Sociodiscursive (ISD) is used, built by Jean Paul Bronckart and collaborators, which consider the social product and language of human psychic development. The methodological approach is qualitative case study type. The Composition of the given data was obtained by means of written work of daily training meetings, diaries of planning and implementation of modeling tasks with students of basic education. The analysis of empirical data was carried out considering the ISD's review procedures: the production context and analysis of the levels of textual analysis-organizational, example and semantic. The organizational level has enabled the identification of the thematic content of the diaries, the actant put in scene in the texts and the predominant discourse types, which showed the relationship of teacher involvement, participant of this research, with the Act Modeling. The enunciatively level assisted the identification and understanding of the teacher's assessments about the thematic content and the semantic level allowed the identification of interpretative figures of the Act. The results indicate that the modeling (re)configurations are marked in the conflicts established in teacher's relationship with: 1) the prescribed work; 2) real of the activity; 3) students; 4) the writing process; 5) your act and the Act modeling; 6) and aspects inherent to the process of mathematical modeling and modeling in education. The following should be noted that the teacher builds gradually the possibility of making education a modeling tool of your work and, with this, it is also (re) built to your agentivity and your students during the Act Modeling, which was accomplished in implementing the task of Modeling in education with students.